Effectiveness of POGIL with SSI Context on Vocational High School Students’ Chemistry Learning Motivation - Yuliastini, I. B.; Rahayu, S.; Fajaroh, F.; Mansour, N. (Jurnal Pendidikan IPA Indonesia, 2018)
This study aimed to examine the difference of Vocational High School students’ learning motivation after they were taught the topic of the electrolyte solution and redox reaction using POGIL model with SSI context, POGIL, and conventional learning. The research design used was quasi-experiment with the model of pre-test and post-test control group design. The research subjects were three classes with the similar initial ability. The data were obtained using SMTSL motivation questionnaire (r = 0.824) and analyzed using ANCOVA. The research results showed a significant difference in learning motivation between students taught using POGIL with SSI context, POGIL, and conventional learning. The students who were taught using POGIL with SSI context had the highest learning motivation compared to those taught using POGIL and conventional learning.